L’applicazione della diffrattometria dei raggi X per l’analisi del cedimento dei componenti meccanici - Mario Guagliano (Fracture and Structural Integrity)
X-ray diffraction is a well-known experimental technique for measuring residual stresses in metallic materials. If XRD is applied to the fracture surface of a broken part it becomes a fractographical technique, that is to say that it is possible to relate the results of the measures to the loading condition that lead a component to fail. In this paper, after an introduction about the technique, XRD fractography is applied to a fatigue failed diesel engine crankshaft. It was possible to determine the load that lead the crankshaft to fail and to evidence some original aspects about the application of this technique to real machine